Using Digital Tools to Enhance Mathematical Modelling Processes - A Swedish Case Study on Effects of Upper Secondary Students' Usage of Digital Tools - Malm, Nina (My University, 2018)
In the latest study plan, the Swedish National Agency for Education has emphasised students’ ability to use digital tools. One subject area for which digital tools shall be used, and where they are known to be advantageous, is mathematical modelling. For example, digital tools are known to extend the range of problem situations that can be handled as well as enabling modellers to focus on modelling and strategic planning rather than calculations. How digital tools should be incorporated into the educational design to exploit these potential benefits is however not trivial. By studying two small groups of upper secondary students, this study was designed to exemplify how the use of digital tools can affect students’ processes and how the design of the learning environment can be adapted to improve the found effects. To gain an understanding in these topics, the students were recorded while engaging in their first modelling experience. Moreover, they were interviewed about their digital tools usage and previous experience of tools. The students were found to benefit from the tools’ collaborative support while remaining unaffected by speed enhancements and decreased cognitive load. In addition, they occasionally engaged in unnecessary tool usage and failed to use a tool’s collaborative features in a new context where they would have benefited from using them. The negative effects were found to be caused by students not having a habit of engaging in metacognitive activity and only consider tools which the teacher had demonstrated. To amend these issues, several instructional strategies were proposed. The ones associated with metacognition involve activities where students design their strategy, and are regularly prompted to present and evaluate it. To expand the number of tools known by students, teachers are recommended to engage students in activities where they acquaint themselves with a tool. In these activities, students practice various competencies associated with efficient tool usage, and their engagement therefore ranges from letting the teacher operate the tool or following a step-by-step instruction to exploring freely.
Keywords: Didaktik; Lärande; Innovation och entreprenörskap (nyttiggörande); Pedagogiskt arbete; Didactics; Learning; Innovation & Entrepreneurship; Pedagogical Work